Micropropagation of two bamboo species Sinocalamus latiflorus and Dendrocalamus asper by tissue culture - Phuong, Vu Ngoc; Tri, Pham Duc; Ai Thuyen, Doan Thi; Nga, Trinh Viet; Du, Tran Xuan; Uyen, Nguyen Van (Academia Journal of Biology, 2015)
Micropropagation of two bamboo species Sinocalamus latiflorus and Dendrocalamus asper by tissue culture